2017
DOI: 10.1007/s10709-017-9970-1
|View full text |Cite
|
Sign up to set email alerts
|

Comparative physical mapping of 18S rDNA in the karyotypes of six leafcutter ant species of the genera Atta and Acromyrmex (Formicidae: Myrmicinae)

Abstract: Leafcutter ants of the Atta and Acromyrmex genera are important plagues in different cultures. Cytogenetic data on chromosome number, morphology, and chromosomal banding pattern are only available for 17 species of leafcutter ants. Molecular cytogenetic data for the detection of ribosomal genes by the FISH technique are scarce, and only 15 Neotropical ant species have been studied. This study aimed to physically map the 18S ribosomal RNA genes (rDNA) of six leafcutter ants belonging to the genera Atta and Acro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 17 publications
0
16
0
Order By: Relevance
“…This was also observed in other fungusgrowing ants such as M. goeldii (Barros et al, 2010(Barros et al, , 2012, A. niger (Barros et al, 2016) and Ac. striatus (Cristiano et al, 2013, Teixeira et al 2017.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This was also observed in other fungusgrowing ants such as M. goeldii (Barros et al, 2010(Barros et al, , 2012, A. niger (Barros et al, 2016) and Ac. striatus (Cristiano et al, 2013, Teixeira et al 2017.…”
Section: Discussionmentioning
confidence: 99%
“…striatus (Cristiano et al, 2013). However, most Acromyrmex (2n = 38) and all Atta species already studied have a single pair of 18S rDNA rich in GC (Barros et al, 2014b(Barros et al, , 2015(Barros et al, , 2016Teixeira et al, 2017). It is suggested that Ac.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations